Wet-adhesive on-skin sensors based on metal–organic frameworks for wireless monitoring of metabolites in sweat - Yang, Xue (2023)
Metal-organic frameworks (MOFs) with well-defined porous structures and tailored functionalities have been widely used in chemical sensing. However, the integration of MOFs with flexible electronic devices for wearable sensing is challenging because of their low electrical conductivity and fragile mechanical properties. Herein, a wearable sweat sensor for metabolite detection is presented by integrating an electrically conductive Ni-MOF with a flexible nanocellulose substrate. The MOF-based layered film sensor with inherent conductivity, highly porous structure, and active catalytic properties enables the selective and accurate detection of vitamin C and uric acid. More importantly, the lightweight sensor can conformably self-adhere to sweaty skin and exhibits high water-vapor permeability. Furthermore, a wireless epidermal nutrition tracking system for the in situ monitoring of the dynamics of sweat vitamin C is demonstrated, the results of which are comparable to those tested by high-performance liquid chromatography. This study opens a new avenue for integrating MOFs as the active layer in wearable electronic devices and holds promise for the future development of high-performance electronics with enhanced sensing, energy production, and catalytic capabilities through the implementation of multifunctional MOFs.